Learning to live with ghosts: spectres of "the Troubles" in contemporary Northern Irish cinema. Issue 3 (3rd July 2021) - Coulter, Colin
ABSTRACT: That Northern Ireland remains profoundly troubled by its own violent past becomes readily apparent in many of the movies that have appeared since the Good Friday Agreement and not least those released since its tenth anniversary. In this article, I provide a broad sketch of recent Northern Irish cinema before moving to a close reading of two critically and commercially acclaimed features released in that period: Hunger (2008) and '71 (2014). The discussion is framed by Mark Fisher's reading of the Derridean notion of "hauntology" and focuses specifically on the idea that the spectre is a figure that is both retrospective and prospective. In their evocation of the ghosts of the Troubles, these movies offer an insight into a society that remains haunted both by the "no longer" of those who died during the conflict and also, perhaps, by the "not yet" of that which suffered a similar fate during the peace process that followed.